Study of hematological parameters in experimental peritonitis on the background of chemotherapeutic drugs - Kosilova, O. Y.; Vovk, O. O.; Ovetchyn, P. V. (Journal of Education, Health and Sport, 2017)
The mice were divided into 9 groups for the experimental part. We have been studying clinical parameters of haemogram: the number of red blood cells, the value of ESR, hemoglobin, leukocyte formula. The data obtained in the study of these indicators in each experimental group of animals were compared with those of control group. Haemograms indicators studied were during the first, third and fifth day of the study. When used amikacin for experimental animals and Gatifloxacin alone and in various combinations (amikacin with gatifloxacin, amikacin combined with coli-proteus bacteriophage, gatifloxacin in combination with coli-proteus bacteriophage, amikacin and gatifloxacin in combination with coli-proteus bacteriophage) it was marked the decrease in the number leukocytes in peripheral blood. The application of coli proteus bacteriophage in the treatment of antibacterial drugs for experimental peritonitis with E.coli on the fifth day resulted normalization of hemorheological changes. On the background of separate antibacterial agent’s application and in combination leucopenia was observed in all animal experimental groups. Based on the experiment the feasibility of a combination of Gatifloxacin coli and proteus bacteriophage during 5 - 7 days 1 time per day depending on these verity of the process for the treatment of patients with peritonitis was proved, and it should be recommended for the treatment of other diseases caused by E. coli.